2021
DOI: 10.3389/frai.2020.609673
|View full text |Cite
|
Sign up to set email alerts
|

EmotionNet Nano: An Efficient Deep Convolutional Neural Network Design for Real-Time Facial Expression Recognition

Abstract: While recent advances in deep learning have led to significant improvements in facial expression classification (FEC), a major challenge that remains a bottleneck for the widespread deployment of such systems is their high architectural and computational complexities. This is especially challenging given the operational requirements of various FEC applications, such as safety, marketing, learning, and assistive living, where real-time requirements on low-cost embedded devices is desired. Motivated by this need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…e scientists also showed that the proposed EmotionNet Nano networks could attain real-time inference speeds (e.g., >25 FPS and >70 FPS at 15 and 30 W, respectively) and great energy efficiency (e.g., >1.7 images/ sec/watt at 15 W) [42].…”
Section: F-scorementioning
confidence: 95%
See 1 more Smart Citation
“…e scientists also showed that the proposed EmotionNet Nano networks could attain real-time inference speeds (e.g., >25 FPS and >70 FPS at 15 and 30 W, respectively) and great energy efficiency (e.g., >1.7 images/ sec/watt at 15 W) [42].…”
Section: F-scorementioning
confidence: 95%
“…e raw data were then preprocessed to eliminate artefacts such as powerline disturbance, which was eliminated using a 50 Hz bandpass filter, proceeded by a glitter bandpass Butterworth filter to retrieve the essential frequencies in the range of 0.05 to 100 Hz to eliminate noise. In our studies, researchers used a Glitter bandpass Butterworth filter to retrieve data from the signal in four main frequency bands: α (2-8 Hz), β (9-14 Hz), θ (15-31 Hz), and c bands (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Glitter Bandpass Butterworth Filtermentioning
confidence: 99%
“…Although results with CNNs in FER have improved consistently through recent years and CNNs have been used in similar applications such as eye gaze detection [ 68 , 69 ], there are few endeavors involving classification on children’s faces. The CAFE data set [ 49 ] currently is the largest publicly available data set of facial expressions from children and is a standard benchmark in the field of FER on children.…”
Section: Discussionmentioning
confidence: 99%
“…Fitur-fitur tersebut dipilih pada tahap pemilihan fitur, sehingga diperoleh beberapa fitur yang mengandung lebih banyak informasi untuk mengklasifikasikan kelas yang berbeda. Pada langkah terakhir (klasifikasi ekspresi wajah), metode pengklasifikasian berbasis machine learning seperti knearest neighbor [8], support vector machine [9], dan neural network [10] terlebih dulu dilatih, kemudian digunakan untuk mengklasifikasikan ekspresi wajah.…”
Section: Pendahuluanunclassified